The listening strategies that students of English Advanced I, at the Foreign Language Department use to improve their listening comprehension skill - Carranza Alvarez, Katty Marilyn
This research was focused on the strategies that students specifically use to improver their listening comprehension skill. It is known that the listening ability is one of the most important skill in foreing language learning because it is developed faster than the other three skill and could affect readind and writing abilities in learning a new language. Scarella& Oxford (1992) Vandergrift (1997). Howatt and Dakin (1974) define listening as speaker's accent or pronuntiation, the grammar and the vocabulary, and grasping the meaning. Besides, research show that the listening skill is employed most frecuently. In daily communication, people spend 45% of the time in listening, 30% on speaking, 16% on reading, and only 9% on writing Feyten (1991). Therefore, strategies for listening and the ability to use them effectively are particularly significant language learning.